KELAYAKAN USAHATANI JAGUNG HIBRIDA (Zea Mays L.) DI NAGARI SALIBUTAN KECAMATAN LUBUK ALUNG KABUPATEN PADANG PARIAMAN - Mahmud; Alin Deri Utama; Anggun Permata Sari (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
The aim of this research is to determine the cost structure of farming and the feasibility of hybrid corn farming in Nagari Salibutan, Lubuk Alung District, Padang Pariaman Regency. This research was carried out in September 2023. The research location was determined purposively, the data used were primary data and secondary data. The analytical method used in this research is a quantitative descriptive method. The results of this research show that (1) The cost structure of hybrid corn farming is divided into 2, namely variable costs and fixed costs with the average variable costs incurred being IDR 16,547,550/ha/mt and fixed costs incurred being IDR 85,183/ha/mt with total costs incurred amounting to IDR 16,632,733/ha/mt (2) Based on the results of the R/C Ratio and BEP analysis which includes: revenue (BEP R), production (BEP Y), price (BEP P) and that hybrid corn farming is worth cultivating, whereas for BEP land area (BEP X) is not worth cultivating from the research results.